Prioritizing Community-Focused Care: The Journal of Student-Run Clinics - Brooke E Rosenbaum; Jessica Kruger; Eric Goldwaser (Journal of Student-Run Clinics, 2016)
In the third issue of the Journal of Student-Run Clinics, we highlight community-focused quality improvement at student-run clinics (SRCs). Given the increasing ubiquity of SRCs in health education and underserved communities, regular efforts must be made to assess and improve quality of care and education. Identification of community-specific health priorities is necessary to implement successful quality improvement strategies at SRCs. Needs assessments can help SRCs objectively identify these priorities, implement effective interventions, and successfully evaluate these interventions. Just as SRCs develop programs based on the needs of their community, the SRC must frequently assess the needs of its student volunteers to provide high quality educational experiences. Focused interventions based on the specific needs of the student population can dramatically improve the educational experience of student volunteers and translate into better patient care.